Checklist of the Arctiidae (Lepidoptera: Insecta) of the continental United States and Canada - Ferguson, Douglas C.; Opler, Paul A. (Zootaxa, 2006)
A checklist of the 282 species of Arctiidae of North America north of Mexico is presented. The list reflects changes in taxonomy and additions to the fauna since publication of the Checklist of the Moths of America North of Mexico in 1983. Pagara Walker, 1856 and Neoplynes Hampson, 1900 are transferred from Lithosiinae to Arctiinae. Lectotypes are designated for Arctia incorrupta Henry Edwards, 1881, and Arctia incorrupta Henry Edwards, 1881. Two new combinations are proposed: Cisthene tenuifascia schwarziorum Dyar, 1899, and Trocodima fuscipes (Grote, 1883). Arachnis citra verna Barnes & McDunnough, 1918 is proposed as a revised status. “Afrida” exegens Dyar, 1922 is reported for North America for the first time, but its subfamily and generic placement are uncertain. Clemensia patella (Druce, 1885) is raised from synonymy with Clemensia albata Packard, 1864. Seventeen taxa are designated as new or revised synonyms: Arctia oithona Strecker, 1878 (= Grammia phyllira (Drury, 1773)); Arctia rectilinea French, 1879 (= Grammia phyllira (Drury, 1773)); Arctia conspicua Stretch, 1906 (= Grammia phyllira (Drury, 1773)); Arctia quadranotata Strecker, 1880 (= Grammia f-pallida (Strecker, 1878)); Apantesis sociata Barnes & McDunnough, 1910 (= Grammia f-pallida Strecker, 1878); Apantesis moierra Dyar, 1914 (= Grammia f-pallida (Strecker, 1878)); Apantesis mormonica Neumoegen, 1885 (= Notarctia arizoniensis (Stretch)); Arctia caja parva Rothschild, 1910 (= Arctia opulenta (Henry Edwards, 1881)); Kodiosoma otero Barnes, 1907 (= Kodiosoma fulva Stretch, 1872); Estigmene arizonensis Rothschild, 1910 (= Estigmene albida Stretch, 1874); Ecpantheria denudata Slosson, 1888 (= Hypercompe scribonia (Stoll, [1790])); Arachnis hampsoni Dyar, 1903 (= Arachnis picta maia Ottolengui, 1896); Arachnis midas Barnes & Lindsey, 1921 (= Arachnis citra verna Barnes & McDunnough, 1918); Arachnis apachea Clarke, 1941 (= Arachnis citra verna Barnes & McDunnough, 1918); Euchaetes pudens (Henry Edwards, 1882) (= Cycnia collaris (Fitch, 1856)); Arctia sciurus Boisduval, 1869 (= Cycnia tenera Hübner, 1827); Pygarctia albistrigata Barnes & McDunnough, 1913 (= Pygarctia pterygostigma Dyar, 1909); and Microdota hemiceras Forbes, 1931 (= Trocodima fuscipes (Grote, 1883)). Halysidota underwoodi Rothschild and H. fuliginosa Rothschild are removed from the North American list because their inclusion was based on